Identifying factors affecting acceptance of virtual reality in classrooms based on technology acceptance model (TAM) / Faizah Abd Majid and Nurshamshida Mohd Shamsudin. - Abd Majid, Faizah; Mohd Shamsudin, Nurshamshida (Universiti Teknologi MARA, 2019)
Technology Acceptance Model (TAM) has received great recognition through the various research conducted on determining users’ acceptance of relevant technology innovation. Past researches have focused on technology innovation in education such as e-learning, Learning Management Systems and online applications. The 21st century teaching and learning framework has identified the relevance of the Internet of Things (IoT) and online applications as part of the teaching and learning process. Besides elearning, MOOCs, Virtual and Augmented Reality have also found their place in the emerging teaching and learning platforms. As Virtual Reality only became popularized in classrooms in the recent years, not much is known about users’ acceptance of this technology innovation in the classroom. This paper, which is based on the TAM, attempted to identify the factors that could affect the respondents’ acceptance of Virtual Reality (VR) in classrooms. Factors on the perceived ease of use (PEoU) and perceived usefulness (PU) affecting the respondents’ attitude and intention to use VR in their classrooms were studied. Employing a quantitative research design, a set of questionnaire based on constructs adapted by Davis (1989) and adapted from past researches (Ngai et al, 2005; Weng et al, 2018, Muhamad Sufi, 2019) was distributed to a group of in-service teachers who were pursuing their postgraduate studies in one of the faculties in Universiti Teknologi MARA. The data was analyzed using SPSS in determining the relationships between the independent variables and the dependent variables. The analysis has further confirmed past research findings. However, in the context of VR, some suggestions to improve current practice are suggested. Policymakers and decision-makers could be enlightened by the present study’s findings. Likewise, teachers may find VR a more convincing platform to be integrated in their classrooms.